Determination and correlation of Avermectin B1a solubility in different binary solvent mixtures at temperatures from (283.15 to 313.15) K. (February 2017) - Shen, Huan; Wu, Songgu; Liu, Yumin; Li, Kangli; Xu, Shijie; Gong, Junbo
Highlights: The solubility of Avermectin B1a in three binary mixtures was determined. The experimental solubility were correlated by three thermodynamic models. Thermodynamic properties of mixing of Avermectin B1a were calculated. Abstract: The solubility of Avermectin B1a (AVM B1a ) in the three binary solvent mixtures, (acetone + water), (acetone + n-hexane) and (isopropanol + n-hexane) was determined gravimetrically with the temperature ranging from 283.15 K to 313.15 K under atmospheric conditions. The experimental results indicate that the solubility of AVM B1a increased with increasing temperature at certain solvent composition, and decreased with increasing mole fraction of water and n-hexane. Besides, the modified Apelblat equation, CNIBS/R-K model and Jouyban-Acree model were employed to correlate the solubility results obtained. All the selected models provide satisfactory results. Furthermore, the mixing thermodynamic properties were calculated based on the NRTL equation, a binary activity coefficient model. We also calculated the thermodynamic properties of the dissolution process of AVM B1a . The calculated results indicate that the dissolution process of AVM B1a in the tested solvents is endothermic and spontaneous.